Aerosol inhalation from spacers and valved holding chambers requires few tidal breaths for children - Schultz, A.; Le Souëf, T.; Venter, A.; Zhang, Guicheng; Devadason, S.; Le Souëf, P. (American Academy of Pediatrics, 2010)
OBJECTIVE: The goal was to determine the number of breaths required to inhale salbutamol from different spacers/valved holding chambers (VHCs). METHODS: Breathing patterns were recorded for 2- to 7-year-old children inhaling placebo from 4 different spacers/VHCs and were simulated by a flow generator. Drug delivery with different numbers of tidal breaths and with a single maximal breath was compared. RESULTS: With tidal breathing, mean inhalation volumes were large, ranging from 384 mL to 445 mL. Mean values for drug delivery with an Aerochamber Plus (Trudell, London, Canada) were 40% (95% confidence interval [CI]: 34%-46%) and 41% (95% CI: 36%-47%) of the total dose with 2 and 9 tidal breaths, respectively. Mean drug delivery values with these breath numbers with a Funhaler (Visiomed, Perth, Australia) were 39% (95% CI: 34%-43%) and 38% (95% CI: 35%-42%), respectively. With a Volumatic (GlaxoSmithKline, Melbourne, Australia), mean drug delivery values with 2 and 9 tidal breaths were 37% (95% CI: 33%-41%) and 43% (95% CI: 40%-46%), respectively (P = .02); there was no significant difference in drug delivery with 3 versus 9 tidal breaths. With the modified soft drink bottle, drug delivery. Drug delivery was not improved with a single maximal breath with any device. CONCLUSION: For young children, tidal breaths through a spacer/VHC were much larger than expected. Two tidal breaths were adequate for small-volume VHCs and a 500-mL modified soft drink bottle, and 3 tidal breaths were adequate for the larger Volumatic VHC. Copyright © 2010 by the American Academy of Pediatrics.